Identification and Control of Chemical Processes Using the Anisochronic Modeling Paradigm. Issue 8 (2015) - Espinoza, M.; Rojas, J.D.; Vilanova, R.; Arrieta, O.
Abstract: An identification methodology is proposed in order to model chemical processes using the anisochronic paradigm. This methodology requires only having the reaction curve of the plant to obtain all the parameters of the model for both over-damped and underdamped processes. On the other hand an optimal tuning for PID controllers considering the closed-loop robustness is also proposed for a given anisochronic model. Both the identification and the control are tested in a pH neutralization process, a well known PID benchmark and in a nonlinear CSTR system, to verify the usefulness of the proposed methodology in chemical processes.